Who is Speaking? The Voice and (In)Visibility of Student Interpreters in Computer-Assisted Interpreting Contexts - Susi Septaviana Rakhmawati; Dewi Kusrini (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
This paper examines the voice and (in)visibility of student interpreters engaged in English–Indonesian diplomatic interpreting tasks under two conditions: with and without Computer-Assisted Interpreting (CAI) tools. Drawing on Hermans’ (1996) framework of the translator’s voice in translated narrative, specifically his three cases of discursive presence (pragmatic displacement requiring intervention for the Implied Hearer, self-reflexive and self-referential engagement with the medium of communication, and contextual overdetermination), and extending these to the spoken, real-time domain of interpreting, this study analyses transcripts and written reflections produced by 40 undergraduate students at an Indonesian university. The analysis also attends to passivisation as an additional marker of the interpreter’s voice. Findings demonstrate that all three of Hermans’ cases are systematically instantiated in student interpreter output, that CAI tool use intensifies certain manifestations of the interpreter’s voice (notably contextual overdetermination and self-referential engagement with the medium) while leaving others unaffected, and that student reflections reveal a metacognitive awareness of their own agency in the interpreting process that is both produced and constrained by the technological environment. The paper argues that making the interpreter’s voice analytically visible is pedagogically valuable: it reveals individual agency, ideological positioning, and identity construction within interpreter-mediated communication.